Preparedness for delivering non-communicable disease services in primary care: access to medicines for diabetes and hypertension in a district in south India. (3rd January 2018) - Elias, Maya Annie; Pati, Manoj Kumar; Aivalli, Praveenkumar; Srinath, Bhanuprakash; Munegowda, Chikkagollahalli; Shroff, Zubin Cyrus; Bigdeli, Maryam; Srinivas, Prashanth N
Abstract : Introduction: Non-communicable diseases (NCDs) have become a major public health challenge worldwide; they account for 28 million deaths per year in low-and-middle-income countries (LMICs). Like many other LMICs, India is struggling to organise quality care for a large NCD-affected population especially at the primary healthcare level. The aim of this study was to assess local health system preparedness in a south Indian primary healthcare setting for addressing diabetes and hypertension. Methods: This paper draws on a mixed-methods research study on access to medicines conducted in Tumkur, Karnataka, India. We used quantitative data from household and health facility surveys, and qualitative data from focus group discussions and in-depth interviews with health workers and patients. We identified systemic drivers that influence utilisation of services at government primary health centres (PHCs) using thematic analysis of qualitative data and a systems framework on access to medicines to assess supply and demand side factors. Results: Majority of households depend on private facilities for diabetes and hypertension care because of the lack of laboratory facilities and frequent medicine stockouts at PHCs. Financial and managerial resource allocation for NCDs and prioritisation of care and processes related to NCDs was suboptimal compared to the prominence of this agenda at global and national levels. Primary healthcare has a limited role even in the activities under the national programme that addresses diabetes and hypertension. Discussion: The study finds critical gaps in the preparedness of PHCs and district health systems in organising and managing care for diabetes and hypertension. Due to the lack of continuous care organised through PHCs, patients depend on expensive and often episodic care in the private sector. There is a need to improve managerial and financial resource allocation towards diabetes and hypertension (and other NCDs) at the district level. Trial registration number: CTRI/2015/03/005640 ; Pre-results.